Karakteristik Lahan Pascatambang Batubara di Loa Janan, Kalimantan Timur : Characteristics of Post-Coal Mining Land in Loa Janan, East Kalimantan - Kamarati, Kiamah Fathirizki Agsa; Noorhamsyah, Noorhamsyah; Ramadan, Laode Muh Asdiq Hamsin; Kardika, Adelia Juli; Saputra, Deka Asmananda (Jurusan Kehutanan, Fakultas Pertanian Universitas Palangka Raya, 2025)
Coal mining activities have a significant impact on land degradation, including loss of topsoil, changes in soil physico-chemical properties, and decreased fertility. This study aims to analyze the soil chemical properties of post-mining land in Loa Janan sub-district, Kutai Kartanegara Regency, which will be used for revegetation activities. The research method used composite soil sampling at three depths of 0-10 cm, 10-20 cm, 20-30 cm on a 50 m × 50 m plot, then analyzed in the laboratory for pH, C-organic, N, P, K, and CEC parameters. The results showed that the soil was acidic at 4.80-4.91 due to pyrite oxidation, with very low C-organic content of 0.88-1.07%, N content of 0.09 - 0.11% very low-low criteria, P content of 0.01%, K content of 0.02-0.04% with very low criteria respectively. Soil CEC is also categorized as low at 14.67-16.38 me/100g due to the lack of organic matter. This condition is also affected by high rainfall which triggers nutrient leaching. This study recommends liming, adding organic matter, and balanced fertilization as rehabilitation strategies to improve soil fertility.